Penerapan LKPD IPA Berbasis Peta Konsep untuk Meningkatkan Hasil Belajar Peserta Didik SMPN 1 Ende - Maria Rosamistika Ema Roma; Maimunah H Daud; Maria Waldetrudis Lidi (Biocaster : Jurnal Kajian Biologi, 2026)
This research is motivated by the low learning outcomes of students due to learning strategies that tend to be one-way and less actively involve students. This study aims to determine the application of Student Worksheets (LKPD) based on concept maps on student learning outcomes on environmental pollution material in class VII of SMPN 1 Ende. This study uses a quantitative method with a true experimental design in the form of a randomized control group pretest-posttest design. The research subjects were 70 students consisting of 35 students in the experimental class and 35 students in the control class. The results showed that the average value of student learning outcomes in the experimental class increased significantly from 49.28 in the pre-test to 97 in the post-test, with an increase of 96.85%. While in the control class, the average value of learning outcomes increased from 50.6 in the pre-test to 64.11 in the post-test, with an increase of 26.71%. The t-test results showed a significance value of 0.000 ≤ 0.05, indicating a significant difference in learning outcomes between the experimental and control classes. Thus, the implementation of concept map-based student worksheets (LKPD) has been proven effective in increasing student activity, engagement, and learning outcomes.